PENINGKATAN HASIL BELAJAR AKIDAH AKHLAK MELALUI STRATEGI TEAM GAMES TOURNAMENT (TGT) DAN MEDIA GAMIFIKASI: STUDI KUASI-EKSPERIMEN DI MA NURUL ISLAM - Fitriyah Kharismah, Fitriyah Kharismah; Puspitarini, Dwi (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2024)
This study aims to examine the effectiveness of the Team Games Tournament (TGT) strategy assisted by Spinning Wheel media in improving Akidah Akhlak learning outcomes among Grade XI students at MA Nurul Islam Lumajang. Using a quasi-experimental design with a pretest-posttest control group, the study involved 56 students selected through purposive sampling. Data were collected using a multiple-choice test and analyzed with an independent t-test. The results show a significant difference in posttest scores between the experimental and control groups (Sig. = 0.001 < 0.05; t = 3.499 > tₜₐ_bₗₑ = 2.221), indicating a positive effect of the TGT strategy combined with gamified media. The findings suggest that integrating cooperative learning with interactive tools enhances student engagement and achievement in religious education, offering a valuable pedagogical approach in the context of Islamic learning.